EXPLORING THE INFLUENCING FACTORS OF EMPLOYEE LOYALTY IN RURAL COMMERCIAL BANKS (CAHIERS MAGELLANES-NS, 2024)
Abstract This study aims to examine factors influencing employee loyalty in rural commercial banks, offering strategic insights for human resource management. We obtained 400 employee responses highlights the significant impact of the working environment on loyalty via online survey. Using a linear regression model with variables such as corporate culture, training, and interpersonal relationships, the results show that employee loyalty is primarily influenced by work environment, training, and interpersonal dynamics. Corporate culture, training and development, performance evaluation, work system, interpersonal relationship, work environment and social environment have a significant positive impact on loyalty. Strategies for enhancing loyalty include improving corporate culture and career development opportunities. The findings urge rural banks to adopt a comprehensive management approach that considers both organizational and external factors affecting employee loyalty.